Reversible adhesion material with strong tangential adhesion, weak normal adhesion and long-term stability as well as preparation method and application thereof

By using a combination of magnetic nanoparticles and liquid silicone rubber in the reversible adhesion material, and performing gradient rearrangement under magnetic field induction, a reversible adhesion material with a wedge-shaped structure is prepared, which solves the problem that existing materials have difficulty in balancing strong tangential adhesion and weak tangential adhesion. Regarding normal adhesion performance, strong tangential adhesion, weak normal adhesion and long-term stability are achieved.

CN119307105APending Publication Date: 2025-01-14SICHUAN UNIV

Patent Information

Application Number
CN202411637632.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing reversible adhesive materials are difficult to take into account both strong tangential adhesion and weak normal adhesion properties, while maintaining stability during long-term use.

Method used

A reversible adhesive material with a wedge-shaped structure was prepared by mixing functionally modified magnetic nanoparticles with liquid silicone rubber and performing magnetic field-induced gradient rearrangement in the mold.

Benefits of technology

It achieves strong tangential adhesion, weak normal adhesion and long-term stable performance, and is suitable for fields such as robotics, aerospace and biomedicine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307105A_ABST
    Figure CN119307105A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of advanced functional materials, and particularly relates to a reversible adhesive material with strong tangential adhesion, weak normal adhesion and long-term stability as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing surface-modified magnetic metal oxide nanoparticles serving as a reinforcement with rubber, pouring the mixture onto an SU-8 soft template with a micro wedge-shaped array structure, inducing the magnetic nano-reinforced particles to generate gradient rearrangement through a magnetic field, and curing and demolding to obtain the wedge-shaped structure gradient-reinforced reversible adhesive material. The composite material has strong tangential adhesion performance, weak normal adhesion performance, long-term stability and the like, and is widely applied to the fields of aerospace, robots, biomedicine and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of reversible adhesion materials, and specifically relates to a reversible adhesion material with strong tangential adhesion, weak normal adhesion and long-term stability, and a preparation method and use thereof. Background Art

[0002] Natural organisms, such as geckos, have excellent adhesion ability on various surfaces, which has aroused widespread research interest. Gecko adhesion can be attached when needed and detached when not needed. Unlike traditional adhesion methods such as gluing, vacuum adsorption, electrostatic interaction and mechanical interlocking, gecko adhesion is basically unaffected by environmental factors, can be reused, and is pollution-free and residue-free when detached. Inspired by the excellent reversible adhesion properties of geckos, a large number of polymer-based reversible adhesion materials have been developed and applied in robotics, aerospace and biomedicine.

[0003] In order to achieve more reliable reversible adhesion performance in practical application scenarios, reversible adhesive materials are usually designed from the perspective of physical structure, with the goal of achieving strong tangential adhesion, weak normal adhesion and long-term performance. Parness et al. first used a double-exposure photolithography mold process to fabricate wedge-shaped reversible adhesive arrays. These adhesives exhibit anisotropic and dynamic adhesive properties and can withstand more than 30,000 connection / separation cycles. 2 The maximum normal force of the patch is 5kPa, and the maximum shear force is 17kPa. Tao et al. used ultra-precision diamond cutting molds to produce wedge-shaped dry adhesives with different inclination angles. The tangential adhesive strength was as high as 50kPa, and the normal adhesive strength reached 10.5kPa. The wedge-shaped structure is a type of gradient structure that is similar to the gradient modulus characteristics of the bristles at the end of the gecko's toes, and the structural advantages of the wedge-shaped structure give it better structural stability than other physical structures (cylinders, etc.). However, the structural optimization of traditional wedge-shaped reversible adhesive materials, mainly including increasing the aspect ratio and increasing the contact area of ​​the inclined surface, will increase its normal adhesion performance while improving the tangential adhesion performance, which is not conducive to the easy desorption performance of the wedge-shaped reversible adhesive material. The research team of Wuhan University used modified Fe 3 O 4 Nanoparticles were filled with polyurethane acrylate polymers in a gradient manner, and finally a gradient modulus inclined cylindrical structure reversible adhesive material was constructed, which has both strong tangential adhesion and long-term usability, but does not have weak normal adhesion. 3 O 4 Nanoparticles are used to prepare wedge-shaped reversible adhesion materials with gradient modulus.

[0004] In summary, in order to meet application requirements, this field urgently needs to develop a reversible adhesion material that has both strong tangential adhesion and weak normal adhesion, so that it can achieve on-demand desorption while having a stable adhesion effect. Summary of the invention

[0005] In view of the problems of the prior art, the present invention provides a reversible adhesion material with strong tangential adhesion, weak normal adhesion and long-term stability, and a preparation method and use thereof.

[0006] A reversible adhesion composite with improved performance is a material with a wedge-shaped structure formed by molding functionally modified magnetic nanoparticles and liquid silicone rubber in a weight ratio of (10-100): (10-200).

[0007] Preferably, the liquid silicone rubber is made of the following raw materials in parts by weight:

[0008] Base polymer 10-200 parts,

[0009] Cross-linking agent 1-100 parts,

[0010] Catalyst 0.1-50 parts.

[0011] Preferably, the base polymer is selected from polysiloxane, and the polysiloxane is selected from vinyl silicone oil;

[0012] And / or, the cross-linking agent is selected from hydrogen-containing silicone oil;

[0013] And / or, the catalyst is selected from platinum catalysts.

[0014] Preferably, the functionally modified magnetic nanoparticles are ferrosoferric oxide nanoparticles with surface coated with silicon dioxide.

[0015] Preferably, the coating thickness of the silicon dioxide is 5-20 nm;

[0016] And / or, the particle size of the magnetic nanoparticles is 50-300 nm;

[0017] And / or, the magnetic nanoparticles are selected from Fe 3 O 4 Nanoparticles.

[0018] The present invention also provides use of the functionally modified magnetic nanoparticles in preparing and / or as reversible adhesion materials.

[0019] The present invention also provides a method for preparing the above-mentioned reversible adhesion composite with improved performance, comprising the following steps:

[0020] Step 1, reacting a base polymer with a crosslinking agent and a catalyst to obtain liquid silicone rubber;

[0021] Step 2, mixing the functionally modified magnetic nanoparticles with liquid silicone rubber to obtain a mixture A;

[0022] Step 3, transferring the mixture A into a mold for pre-curing;

[0023] Step 4, during the pre-curing process, an external magnetic field is introduced to induce gradient rearrangement of the functionally modified magnetic nanoparticles to obtain a composite 1;

[0024] Step 5, curing and demolding the composite 1 to obtain a reversible adhesive material with a micro-wedge-shaped structure.

[0025] Preferably, in step 3, the mold is selected from a SU-8 mold for forming a micro-wedge array structure; the pre-curing conditions are: a temperature of 30-80° C. and a time of 0.3-10 h;

[0026] and / or, in step 4, the external magnetic field is selected from a samarium cobalt magnet;

[0027] And / or, in step 5, the curing conditions are: temperature of 50-150°C, time of 1-10h; the size of the micro-wedge-shaped structure is (10-50)μm×(10-50)μm×(10-100)μm, the aspect ratio is 1-5, and the center distance between adjacent wedge-shaped microstructures is 10-50μm.

[0028] The present invention also provides use of the reversible adhesion composite with improved performance in the preparation and / or as a reversible adhesion material.

[0029] Preferably, the reversible adhesion material has strong tangential adhesion, weak normal adhesion and long-term stability.

[0030] The present invention provides a reversible adhesion material with strong tangential adhesion, weak normal adhesion and long-term stability. The modified ferroferric oxide nanoparticles are mixed with liquid silicone rubber as a reinforcement and then poured onto a SU-8 mold with a micro-wedge array structure to prepare a wedge-shaped gradient-enhanced reversible adhesion material. As a typical magnetic nanomaterial, ferroferric oxide can respond quickly to a magnetic field. This property can be used to induce rearrangement of the ferroferric oxide uniformly dispersed inside. 3 O 4Under the induction of magnetic field, nanoparticles are distributed in a gradient inside the microstructure, further increasing the modulus difference from the tip to the root of the microstructure, while ensuring the flexibility of the tip of the microstructure. Therefore, under the conditions of normal preload and shear force, a closer conformal contact will be formed when the surface microstructure contacts the adhesion interface after deformation, thereby generating greater tangential adhesion performance; and the elastic potential energy stored when the surface microstructure is bent and deformed enables it to be easily separated from the adhesion interface after the normal preload and shear force are removed. Therefore, the composite material provided by the present invention has strong tangential adhesion performance, weak normal adhesion performance and long-term stability, and is widely used in robotics, aerospace, biomedicine and other fields.

[0031] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0032] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A synthetic route for wedge-shaped gradient modulus reversible adhesion materials.

[0034] Figure 2 The morphology and EDS element distribution results of wedge-shaped microcolumns.

[0035] Figure 3 The tangential adhesion performance characterization results of different wedge-shaped reversible adhesion materials. (a) Schematic diagram of tangential adhesion performance test; (b) Tangential adhesion force-time curve of sample 0nm-WG under different preloads; (c) Tangential adhesion force-time curve of sample 50-300nm-WG under different preloads.

[0036] Figure 4 The normal adhesion performance characterization results of different wedge-shaped reversible adhesion materials. (a) Schematic diagram of normal adhesion performance test; (b) Normal adhesion force-time curve of sample 0nm-WG under different preloads; (c) Normal adhesion force-time curve of sample 50-300nm-WG under different preloads; (d) Normal adhesion strength characterization results under different preloads.

[0037] Figure 5The long-term performance characterization results of different wedge-shaped gradient enhanced reversible adhesion materials. (a) Tangential cyclic adhesion force-time curve of 0nm-WG sample under 0.2N preload; (b) Average value of maximum tangential adhesion force of 0nm-WG sample under 0.2N preload; (c) Tangential cyclic adhesion force-time curve of 50-300nm-WG sample under 0.2N preload; (d) Average value of maximum tangential adhesion force of 50-300nm-WG sample under 0.2N preload. DETAILED DESCRIPTION

[0038] In the following examples and experimental examples, reagents and raw materials not specifically described are all commercially available products.

[0039] Example 1: Preparation of wedge-shaped gradient modulus reversible adhesion material

[0040] 1. Surface coating SiO 2 Fe 3 O 4 Preparation of nanoparticles

[0041] First, 2 g Fe 3 O 4 Nanoparticles (Fe 3 O 4 NPs, 50-300nm, 97% trace metals basis, Shanghai Aladdin reagent) were uniformly dispersed in 500ml of anhydrous ethanol. Subsequently, 2ml of tetraethyl silicate (99.99% trace metals basis, Shanghai Aladdin reagent) was added dropwise and ultrasonic treatment was continued for 3 hours. Finally, the treated particles were washed several times with deionized water and fully dried to obtain surface-coated SiO 2 The thickness of Fe is 10nm 3 O 4 Nanoparticles (Fe 3 O 4 @SiO 2 NPs).

[0042] 2. Preparation of 50-300nm-wedge-shaped gradient-enhanced reversible adhesion material (50-300nm-WG)

[0043] According to step 1, 50-300nm Fe 3 O 4 NPs were pretreated to obtain Fe 3 O 4 @SiO 2 NPs, firstly, 100g of vinyl silicone oil, 3g of hydrogenated silicone oil, and 0.2g of platinum catalyst were mixed to obtain liquid silicone rubber, and then 15% by mass of Fe 3 O4 @SiO 2 After the NPs were fully mixed with the liquid silicone rubber, they were transferred to the SU-8 mold that molded the micro-wedge array structure ( Figure 1 b) to achieve uniform thickness. The mold was transferred to a vacuum oven for degassing, and then heated to 60°C and kept warm for 0.5 hours for pre-curing. During the pre-curing process, a samarium cobalt magnet was placed directly above the mold to apply a vertical magnetic field, thereby inducing Fe 3 O 4 @SiO 2 The NPs are rearranged in a gradient (more nanoparticles are filled at the bottom of the wedge structure and fewer nanoparticles are filled at the tip). Then, the magnetic field is removed and the temperature is raised to 80°C for 3 hours for final curing. Finally, the cured material is peeled off from the mold ( Figure 1 c). The size of the obtained micro-wedge-shaped structure is 20 μm×20 μm×40 μm, the aspect ratio is 2, and the center distance between adjacent wedge-shaped microstructures is 30 μm, resulting in a 50-300 nm-WG sample.

[0044] Comparative Example 1

[0045] This comparative example provides the control samples used in the experiment:

[0046] 1. 0nm-WG

[0047] The difference from the 50-300nm-WG sample is that this sample does not have the surface modified Fe 3 O 4 The rest of the preparation method is the same as that in Example 1.

[0048] The technical solution of the present invention is further illustrated by experiments below.

[0049] The 50-300nm-WG and 0nm-WG samples used in this experimental example were prepared according to the method of Example 1 or Comparative Example 1.

[0050] Experimental Example 1: Characterization of surface morphology and iron element distribution of wedge-shaped gradient modulus reversible adhesion material

[0051] 1. Experimental Methods

[0052] The morphology of the wedge-shaped gradient modulus reversible adhesion material was observed using a field emission scanning electron microscope (SEMApreo S, Thermo Fisher Scientific) under high vacuum conditions.

[0053] The Fe element distribution image of a single row of wedge-shaped columns was measured by energy spectrum (EDS Aztec X-Max80, Oxford Instruments), and the influence of the gradient distribution of nanoparticle reinforcement under magnetic field induction was obtained.

[0054] 2. Experimental Results

[0055] Figure 2 The surface morphology characteristics (SEM) of the micropillars of the two samples and the energy dispersive spectroscopy (EDS) imaging results of a single row of pillars. The magnetic field induction does not change the surface morphology of the micropillars mixed with magnetic nanoparticles; the EDS results of the iron distribution in the samples show that the particle size distribution of the 50-300nm-WG sample is wider, forming an ideal gradient distribution in the wedge-shaped micropillars.

[0056] The experimental results show that the viscosity of the silicon matrix limits the rearrangement of smaller nanoparticles induced by the magnetic field. The reinforcements with smaller particle sizes are evenly distributed in the microcolumn, while the reinforcements with larger particle sizes migrate to the bottom under the action of the magnetic field, thereby achieving gradient enhancement of the entire wedge-shaped microcolumn.

[0057] Experimental Example 2: Characterization of Shear Adhesion Performance of Wedge-Shaped Gradient Modulus Reversible Adhesion Materials

[0058] 1. Experimental Methods

[0059] The tangential adhesion performance of the wedge-shaped gradient modulus reversible adhesion material was evaluated by a typical load-drag-tension test using a tribometer (UMT TriboLab, Bruker, USA). The UMT TriboLab is equipped with a lateral positioning motor with an encoder system and a test prototype on a vertical positioning system (GPS), which can accurately control the friction reciprocating motion and load. The shear force on the indenter is measured by linear reciprocating motion at room temperature. A stainless steel hemispherical indenter is pressed on the surface of the sample wedge column with a preload force, and the sliding speed and stroke length of the spherical indenter are set respectively. The test is repeated five times at different positions on the sample surface to obtain the standard deviation.

[0060] 2. Experimental Results

[0061] The tangential adhesion performance of the samples was evaluated using a typical load-drag-tension test (LDP). During the test, the friction pair was in contact with the sample column and a normal preload of 0.2N, 0.3N, and 0.4N was applied. Under these preloads, the actual contact area between the wedge-shaped gradient modulus reversible adhesion material and the friction pair was approximately 0.064cm 2 、0.079cm 2 and 0.085cm 2 After reaching the set preload, the friction pair applies a 5mm long reciprocating shear displacement to the sample at a rate of 0.1mm / s for 5 times, and the shear force is recorded during the entire test. Figure 3 As shown in a. Figure 3b, 3c show the tangential adhesion force-time curves of different wedge-shaped gradient modulus reversible adhesion materials obtained from LDP tests.

[0062] The results show that the tangential adhesion of all reversibly adhesive materials increases with increasing preload, with the 50-300nm-WG samples showing higher tangential adhesion at all preloads.

[0063] Experimental Example 3: Characterization of the Normal Adhesion Performance of Wedge-Shaped Gradient Modulus Reversible Adhesion Materials

[0064] 1. Experimental Methods

[0065] The normal adhesion performance test is carried out using RSAG2 solid analyzer. RSA G2 is a very precise solid mechanics analysis device that can provide 0.01mN force control accuracy and 1nm displacement control accuracy. Figure 4 As shown in a, the sample (size 1cm 2 ) is fixed on the upper circular plate, while the adhesive substrate (silicon wafer) is fixed on the lower circular plate, ensuring that the two planes are aligned parallel. The normal preload of the sample pressed on the substrate surface is set, and after maintaining the preload for 60 seconds, the sample is pulled out at a speed of 3mm / s; as the preload increases, the wedge-shaped microstructure bends under the applied load, forms a good conformal contact with the silicon wafer, and separates when an external force is applied. The pull-off force is recorded throughout the process, and the normal adhesion strength (separation stress divided by contact area) is obtained from the pull-off force-time curve; the substrate surface is cleaned with ethanol after each test, and the test is repeated 5 times.

[0066] 2. Experimental Results

[0067] The normal adhesion properties under preloads of 0.05N, 0.5N, 1.0N, 1.5N, and 2N were measured using an RSA G2 solid analyzer. The pull-off force-time curves are shown in Figure 2. Figure 4 b and 4c. The normal adhesion test results of reversible adhesion materials under different preloads are used to understand the effect of gradient reinforcement on the normal adhesion effect. Under micro-contact conditions (0.05N preload), both wedge-shaped gradient modulus reversible adhesion materials exhibit similar and sufficiently small normal adhesion forces. As the applied normal preload increases, the reversible adhesion material produces a larger normal adhesion force. It is worth noting that when the preload reaches 1N, the normal adhesion force of the control sample 0nm-WG shows a significant upward trend, while the normal adhesion force of the gradient reinforced sample 50-300nm-WG does not show a significant increase.

[0068] Further analysis of the normal adhesion strength calculation results ( Figure 4d) It can be seen that when the preload is 1N, the pull-off strength of 0nm-WG is 6 times that of 0.05N preload; when the preload is 2N, the pull-off strength of 0nm-WG is 21 times that of 0.05N preload; when the preload increases to 2N, the normal adhesion strength of 50-300nm-WG is even less than the normal adhesion strength of the control sample 0nm-WG under 1N preload. In addition, it is found that the normal adhesion strength of the gradient-enhanced sample 50-300nm-WG is less affected by the change of preload force. When the preload is 2N, the normal adhesion strength of 50-300nm-WG is only 1.8 times that of the sample under 1N preload.

[0069] Experimental results show that the gradient enhancement of nanoreinforcements makes the wedge-shaped gradient modulus reversible adhesion material exhibit excellent weak normal adhesion properties.

[0070] Experimental Example 4: Characterization of long-term performance of wedge-shaped gradient modulus reversible adhesion materials

[0071] 1. Experimental Methods

[0072] The long-term performance of the reversible adhesion material was evaluated by a typical load-drag-tension test using a tribometer (UMT TriboLab, Bruker, USA). During the test, the friction pair contacted the sample column and applied a normal preload of 0.2N. After reaching the set preload, a reciprocating shear motion was performed on a 5mm long area at a rate of 3mm / s for 300 times.

[0073] 2. Experimental Results

[0074] The tangential adhesion-time curve is shown in Figure 5 a and 5c. Even the tangential adhesion time curve of the sample 0nm-WG without gradient enhancement did not show a significant decrease in force value, which means that 300 cycles of tangential adhesion did not cause large-scale structural damage to the wedge structure, and the wedge structure has excellent structural stability. The maximum tangential adhesion force in each reciprocating shear process was selected and averaged in groups of 10. The results are shown in Figure 5 b and 5d. The results show that the maximum tangential adhesion of sample 0nm-WG shows a clear downward trend with the increase of the number of cycles during the whole process, which indicates that the wedge-shaped structure also has the problem of performance degradation during multiple tangential wear processes. The maximum tangential adhesion of sample 50-300nm-WG even shows a trend of first increasing and then stabilizing. The heat generated during the rapid tangential friction makes the wedge-shaped microstructure have a more flexible deformation ability.

[0075] Experimental results show that the gradient enhancement of nanoreinforcements makes the wedge-shaped gradient modulus reversible adhesion material have outstanding long-term stability.

[0076] In summary, the 50-300nm-wedge-shaped gradient-enhanced reversible adhesion material of the present invention uses nano-enhanced particles with a wide particle size distribution of 50-300nm, which can migrate and rearrange under the induction of a magnetic field to achieve gradient enhancement of the entire wedge-shaped microcolumn, and the reversible adhesion material has the properties of strong tangential adhesion, weak normal adhesion and long-term stability.

Claims

1. A reversible adhesion composite with improved performance, characterized in that: The invention relates to a wedge-shaped material composed of functionally modified magnetic nanoparticles and liquid silicone rubber and molded in a weight ratio of (10-100): (10-200).

2. The reversible adhesion composite with improved performance according to claim 1, characterized in that: The liquid silicone rubber is made of the following raw materials in parts by weight: Base polymer 10-200 parts, Cross-linking agent 1-100 parts, Catalyst 0.1-50 parts.

3. The reversible adhesion composite with improved performance according to claim 2, characterized in that: The base polymer is selected from polysiloxanes; And / or, the cross-linking agent is selected from hydrogen-containing silicone oil; And / or, the catalyst is selected from platinum catalysts.

4. The reversible adhesion composite with improved performance according to claim 1, characterized in that: The functionally modified magnetic nanoparticles are ferroferric oxide nanoparticles with surfaces coated with silicon dioxide.

5. The reversible adhesion composite with improved performance according to claim 4, characterized in that: The coating thickness of the silicon dioxide is 5-20nm; And / or, the particle size of the magnetic nanoparticles is 50-300 nm; And / or, the magnetic nanoparticles are selected from Fe3O4 nanoparticles.

6. Use of functionally modified magnetic nanoparticles for preparing and / or as reversible adhesion materials.

7. A method for preparing the reversible adhesion composite with improved performance according to any one of claims 1 to 5, comprising the following steps: Step 1, reacting a base polymer with a crosslinking agent and a catalyst to obtain liquid silicone rubber; Step 2, mixing the functionally modified magnetic nanoparticles with liquid silicone rubber to obtain a mixture A; Step 3, transferring the mixture A into a mold for pre-curing; Step 4, during the pre-curing process, an external magnetic field is introduced to induce gradient rearrangement of the functionally modified magnetic nanoparticles to obtain a composite 1; Step 5, curing and demolding the composite 1 to obtain a reversible adhesive material with a micro-wedge-shaped structure.

8. The preparation method according to claim 7, characterized in that: In step 3, the mold is selected from a SU-8 mold for forming a micro-wedge array structure; the pre-curing conditions are: a temperature of 30-80° C. and a time of 0.3-10 h; and / or, in step 4, the external magnetic field is selected from a samarium cobalt magnet; And / or, in step 5, the curing conditions are: temperature of 50-150°C, time of 1-10h; the size of the micro-wedge-shaped structure is (10-50)μm×(10-50)μm×(10-100)μm, the aspect ratio is 1-5, and the center distance between adjacent wedge-shaped microstructures is 10-50μm.

9. Use of the reversible adhesion composite with improved properties according to any one of claims 1 to 5 in the preparation and / or as a reversible adhesion material.

10. The use according to claim 9, characterized in that The reversible adhesion material has strong tangential adhesion, weak normal adhesion and long-term stability.

Citation Information

Patent Citations

  • Meanwhile, adhesion force and friction force are enhanced

    CN111333882A

  • High-performance bionic reversible adhesion material and application thereof

    CN117986593A

  • On / off reversible adhesive

    US20070251648A1

Cited By

  • Modified polymethylvinylsiloxane, preparation and application thereof, and adhesive material

    CN121378757A